INTERNALISASI NILAI NILAI ISLAM MODERAT DALAM PENGAJIAN MUNAJAT JALANAN AGUS ROJIB IZZIL MUTTAQIN: (STUDI ETNOGRAFI PADA KAUM MARGINAL MALANG) - Ahmad Rizal (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
Marginalized people, who often experience social, economic, and even spiritual marginalization, get new space to grow and develop in a more inclusive and loving environment. Therefore, the background of this thesis examines in depth the process of internalizing moderate Islamic values through the Street Munajat Study program intended for the Marginalized in Malang. This study uses a qualitative approach with an ethnographic design, which allows researchers to comprehensively explore the meanings contained in the study group. Data were collected through various techniques such as participatory observation, in-depth interviews, focus group discussions (FGDs), field notes, and visual and audio documentation. Information was obtained from various sources, including the study group caregivers, marginal community members, and related figures, who acted as key informants. Data analysis was carried out in stages through the process of editing, classification, analysis, and drawing conclusions, using a triangulation approach to verify the validity of the data. Researchers also conducted continuous in-depth observations (persistent observation) and compiled detailed descriptions (thick descriptions) to present a complete contextual picture. The results of this study indicate: A) Moderate Islamic values contained in the Agus Rojib Izzil Muttaqin Street Munajat study: 1. Tawassuth (Middle Attitude), 2. Tasamuh (Tolerance), 3. Rahmah (Compassion) B) The Process of Internalizing Moderate Islamic Values in Street Munajat Study for the Marginalized in Malang. 1. Inclusive and Humanistic Approach, 2. Conveying Values Through Simple Language C) Results of Internalizing Moderate Islamic Values in Street Munajat Study for the Marginalized in Malang. 1. Changes in Religious Mindset, 2. Increasing Social Solidarity